Measurement and modelling of transpiration losses in packaged and unpackaged strawberries. (October 2018) - Bovi, Graziele G.; Rux, Guido; Caleb, Oluwafemi J.; Herppich, Werner B.; Linke, Manfred; Rauh, Cornelia; Mahajan, Pramod V.
Abstract : Transpiration and respiration are physiological processes well-known as major sources of fresh produce mass loss. Besides causing impairment of external quality, it is associated with economic loss since it inevitably decreases saleable weight. To prevent postharvest mass losses, by improved modified atmosphere and humidity packaging, comprehensive knowledge on the mechanistic basis of both processes and their interactions is essential. The objective of this study was to evaluate the contribution of these processes on mass loss of packaged and unpackaged strawberries. Experiments on a single strawberry were performed at 4, 12 and 20 °C; and 76, 86, 96 and 100% RH. Mass loss was also investigated as a function of number of strawberries and package volume at 12 °C. A combined model based on Arrhenius equation and Fick's first law of diffusion for an unpackaged single strawberry and a model based on degree of filling was developed and validated with packaged strawberries. These models have potential application towards the selection of optimal moisture control strategies for strawberries. Highlights: Fresh produce transpires even at 100% RH. Transpiration at 100% RH resulted from a higher fruit body temperature. Package headspace played a major role on mass loss.